HUBUNGAN KEPEMIMPINAN INOVATIF DAN KUALITAS SUMBER DAYA MANUSIA DENGAN KAPASITAS MANAJEMEN INOVASI DI DINAS KESEHATAN KOTA SEMARANG - Dzakiyyah Rahmawati, Yulita; Santoso, R. Slamet; Subowo, Ari (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2024)
The purpose of the study was to determine the relationship between Innovative Leadership (X1) with Innovation Management Capacity (Y), the relationship between Human Resource Quality (X2) and Innovation Management Capacity (Y), and the simultaneous relationship between Innovative Leadership (X1) and Human Resource Quality (X2) with Innovation Management Capacity (Y) in Semarang City Health Office. This study used quantitative methods through data collection in the form of questionnaires and employee interviews based on proportional random sampling techniques with as many as 48 respondents. The analysis techniques used are validity test, reliability test, Kendall Tau correlation, Kendall Concordance, and Coefficient of Determination. The results showed that there was a positive and significant relationship between Innovative Leadership (X1) and Innovation Management Capacity (Y) of 0,749 and the coefficient of determination contributed 69,5%%. The correlation of other variables shows that there is a positive and significant relationship between the Quality of Human Resources (X2) with the Innovation Management Capacity (Y) of 0,723 and the coefficient of determination contributes 69,7% and simultaneously there is a positive and significant relationship between Innovative Leadership (X1) and Human Resource Quality (X2) with Innovation Management Capacity (Y) of 0,482 and the coefficient of determination contributes 79,5%.